Carbonization Time Optimization In The Preparation Of Coconut Pulp Based Activated Carbon For Thermoelectric Materials - Febrian, Nanda; Darvina, Yenni; Ramli, Ramli; Hidayat, Rahmat (Department of Physics, Universitas Negeri Padang, 2024)
In this study utilizing coconut pulp as an ingredient in making activated carbon for thermoelectric materials From the research that has been done, it is not yet known the best carbonization time on coconut pulp activated carbon for thermoelectric materials. Therefore, this study aims to determine the optimization of carbonization time on coconut pulp activated carbon for thermoelectric materials. The coconut pulp was dried using an oven at 105ºC and then carbonized using a furnace. Carbonization time variations used were 10 minutes, 15 minutes, and 20 minutes with temperature variations from previous research, namely 300ºC. Then the results of carbonization were mashed using a mortar and pestle and filtered using a 120 mesh sieve. Carbon was activated with 0.5 M HCl (1:10) as much as 25 grams for 24 hours. After activation, the carbon was filtered, washed with distilled water and dried using an oven. Then the coconut pulp activated carbon was characterized by testing water content, vapor content, ash content, and bound carbon content. The test results show that based on SNI 06-3730-1995 the lowest water content is at 10 minutes carbonization time which is 1.72%, the lowest steam content is at 10 minutes carbonization time which is 8.54%, the lowest ash content is at 20 minutes carbonization time which is 0.55%, and the highest bound carbon content is at 10 minutes carbonization time which is 90.65%. The results showed that the optimization of carbonization time on coconut pulp activated carbon for thermoelectric materials was 10 minutes.